2021
DOI: 10.2337/db20-0873
|View full text |Cite
|
Sign up to set email alerts
|

ENTPD3 Marks Mature Stem Cell–Derived β-Cells Formed by Self-Aggregation In Vitro

Abstract: Cell cultureGeneration of stem cell derived beta-like cells from human embryonic stem cells and from induced pluripotent stem cells MEL1 human embryonic stem cells (hESC) containing the INS GFP/W reporter 18 (referred to as pINSGFP throughout the manuscript) and sub-clones thereof 19,31 , type 1 diabetes patient induced pluripotent stem cells (T1D-iPSC) 24 (Supp. Fig 8 .) and iPSC from a healthy donor 48 (Supp. Fig. 9), as well as pNKX6.1 GFP reporter iPSC 46 were employed in this study. All iPSC lines were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…The raptor subunit of the mTORC1 complex is necessary for the regulation of beta cell function, autophagy and repression of disallowed genes [24][25][26] whereas mTORC2 complexes, which function through the presence of the rictor subunit, have been implicated in the mediation of beta cell mass and proliferation, islet cytoarchitecture and modulation of GSIS through activation of protein kinase Cα [24,27,28]. Postnatal rearrangement of islet cytoarchitecture is another key process in mature functionality seen in vivo [29,30] as well as in recent models of SC-islet maturation in vitro [31]. Modulation of these processes through mTORC2-mediated signalling may indeed be responsible for islet reorganisation, prior to downregulation of mTOR signalling, and the onset of functional maturity.…”
Section: Monohormonal Insulin Expression Production and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The raptor subunit of the mTORC1 complex is necessary for the regulation of beta cell function, autophagy and repression of disallowed genes [24][25][26] whereas mTORC2 complexes, which function through the presence of the rictor subunit, have been implicated in the mediation of beta cell mass and proliferation, islet cytoarchitecture and modulation of GSIS through activation of protein kinase Cα [24,27,28]. Postnatal rearrangement of islet cytoarchitecture is another key process in mature functionality seen in vivo [29,30] as well as in recent models of SC-islet maturation in vitro [31]. Modulation of these processes through mTORC2-mediated signalling may indeed be responsible for islet reorganisation, prior to downregulation of mTOR signalling, and the onset of functional maturity.…”
Section: Monohormonal Insulin Expression Production and Retentionmentioning
confidence: 99%
“…Inhibition of the transforming growth factor β receptor 1 (TGFBR1, also known as ALK5) during SC-islet maturation has been shown to increase many beta cell marker genes, including MAFA [ 5 ]. However, more recent studies have shown either a marked improvement of SC-islet beta maturation in the absence of ALK5 inhibitors [ 132 ] or, in contrast, an increase in insulin expression in the presence of ALK5 inhibition [ 31 ]. Another member of the superfamily, bone morphogenetic protein 4 (BMP4), may also aid in the postnatal maturation of beta cell function following temporally controlled release from islet pericytes [ 133 ].…”
Section: Signalling Pathways and Gene Markers Of Beta Cell Maturationmentioning
confidence: 99%
“…The iPSC lines, 1-018 and 1-023, were differentiated to sBC as previously described ( 22 ). Donor 2395 iPSC were maintained on Matrigel-coated 6 well plates in mTeSR+ medium (StemCell Technologies) and differentiated to sBC as previously described ( 27 , 28 ). Differentiation to sBC was carried out in suspension‐based, low attachment suspension culture plates as described ( 29 ) or in an ABLE bioreactor magnetic stirring system (Reprocell, Beltsville, MD, USA) as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, published data indicate that sBCs exhibit distinct degrees of functionality (often referred as maturity). Indeed, in-depth characterization has revealed the presence of distinct subpopulations even in sBCs with dynamic insulin secretion, a hallmark of maturity [ 24 ]. Additional refinements of late-stage culture conditions might allow the capture of a more mature sBC phenotype, as current medium formulations fail even at preserving function in isolated cadaveric islets.…”
Section: β-Cell Replacementmentioning
confidence: 99%